Peripeteia: Rehearsing Against the End of the World. Issue 4 (December 2021) - Jakovljević, Branislav; Looser, Diana
Abstract : How can performance help us to think about the problem of climate change and its integral relationships to social and political frameworks? What directions do societies and arts need to take in order to forge different futures? Reflections on the proposals put forward in this installment of the special issue on Peripeteia raise questions toward further conversation.